FORECAST OF DEVELOPMENT OF THE OIL AND PIPE INDUSTRY up to 2020 - A. Borozdin (Вестник университета)
Prediction of oil production and consumption of pipe products to take into account the significant changes in the development of the industry. The problem of the production, transportation and refining of oil and gas in our country is always up to date. In the oil industry, metallurgy in all processes is important. Metallurgy in offshore oil and natural gas occur to their processing and use as a finished product.